Anti-Oxidant and Anti-Microbial Activities of [ZnO: CoO/ Eugenol] and [ZnO: Fe2O3/ Eugenol] Nanocomposites - Fatin A. Al-jubouri; Basim I. Al-Abdaly (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
Metal oxide nanocomposites (MONCs) manufacturing is increasingly gaining popularity. The primary cause of this is the broad range of applications for such materials, which include fuel cells, photovoltaics, cosmetics, medicine, semiconductor packing materials, water treatment, and catalysts. Due to their size, stability, high surface area, catalytic activity, simplicity in fabrication, and selectivity for particular reactions. The MONCs with various morphologies have been created by physical, chemical, and biological processes, such as sol-gel, hydrothermal, co-precipitation, solvothermal, and microwave irradiation. Eugenol (4-allyl-2-methoxyphenol) is a major component of clove essential oil and it was found in various plant groups, has been widely utilized, and famously stated to have a variety of important biological activities. It is a good starting material for the synthesis of a wide variety of derivatives with different activity. Due to the presence of many functional groups in its structure, including allyl (-CH2-CH=CH2), phenol (-OH), and methoxy (-OCH3). The eugenol was taken with metal oxides (zinc cobalt oxides ZnO: CoO) to synthesis [ZnO: CoO/ Eug] and (zinc ferric oxides ZnO: Fe2O3) to synthesis [ZnO: Fe2O3/ Eug] as nanocomposites by hydrothermal method and characterization the compounds using: (FT-IR, AFM, SEM, EDX, XRD) techniques. Then, they tested their biological activities through antimicrobial and antioxidant.